Training manikin for neonate management with surgically implanted devices: ConectNeo (Research, Society and Development, 2021)
Objective: to develop and validate a neonatal mannequin for skills training in handling the neonate with surgically implanted invasive devices. Method: this is a descriptive quantitative research, with the participation of 21 experts in the process of evaluating the mannequin for validation, respecting all ethical aspects involving research of this nature. To assess the didactic value of the developed product, a validation test was proposed, consisting of experimentation with the model, application of a self-instructional questionnaire containing sociodemographic questions and ten Likert-type scale for each device evaluated. Results and discussion: 10 devices were evaluated in the complete model and they were external ventricular shunt, ventricular peritoneal shunt, tracheostomy cannula, gastrostomy tube, peritoneal dialysis catheter, umbilical catheter, mediastinal drain, chest drain, central venous catheter, catheter peripherally inserted center, all for neonatal use. The domains evaluated form aesthetics, strength, use for teaching, sensory issue, anatomical references and relevance. All of the proposed devices obtained more than 98.1% of grade, and in the general evaluation of the complete model it obtained 99.3%. Conclusion: given the complexity of the topic and there being no model available on the market with such developed characteristics, the proposed objective was achieved by the Innovation and Technology Transfer Center validation and patenting of a new concept of neonatal mannequin, with opportunity for innovation, where the validation test allowed infer good acceptance of the model in practice, proving to be an effective and viable alternative for teaching the management of newborns who have devices that were surgically implanted.